2022
DOI: 10.1172/jci.insight.145653
|View full text |Cite
|
Sign up to set email alerts
|

Epac1–/– and Epac2–/– mice exhibit deficient epithelial Na+ channel regulation and impaired urinary Na+ conservation

Abstract: Exchange proteins directly activated by cAMP (Epacs) are abundantly expressed in the renal tubules. We used genetic and pharmacological tools in combination with balance, electrophysiological, and biochemical approaches to examine the role of Epac1 and Epac2 in renal sodium handling. We demonstrate that Epac1 –/– and Epac2 –/– mice exhibit a delayed anti-natriuresis to dietary sodium restriction despite augmented aldosterone levels. This was associated with a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Single-channel activity of Yoda-1-activated Piezo1 channel was determined in cell-attached patches on the apical membrane in freshly isolated split-opened collecting ducts and on the basolateral membrane in freshly isolated collecting ducts, as shown in representative images in Figure 6 . Gradual activation of Piezo1 by Yoda-1 was detected under voltage-clamp conditions (− Vp =− 60 mV), as previously described ( 47 , 53 ). To assess single channel conductance, pipette voltage was changed from -Vp = −100 mV to +60 mV for at 30 s. PCs and ICs were visually identified by their polygonal and round shape, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Single-channel activity of Yoda-1-activated Piezo1 channel was determined in cell-attached patches on the apical membrane in freshly isolated split-opened collecting ducts and on the basolateral membrane in freshly isolated collecting ducts, as shown in representative images in Figure 6 . Gradual activation of Piezo1 by Yoda-1 was detected under voltage-clamp conditions (− Vp =− 60 mV), as previously described ( 47 , 53 ). To assess single channel conductance, pipette voltage was changed from -Vp = −100 mV to +60 mV for at 30 s. PCs and ICs were visually identified by their polygonal and round shape, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the cAMP pathway promoted ENaC trafficking to the apical membrane [46] and increased ENaC open probability [47]. Exchange proteins directly activated by cAMP (Epacs) are abundantly expressed in the renal tubules and constitutive knockout mice for Epac1 and Epac2 provided evidence that single or combined deletion impaired stimulation of ENaC and compromised renal sodium conservation in response to dietary sodium deficiency [48 ▪ ]. Mammalian Ste20-like protein kinase 3 (MST3/STK24) is mainly expressed in the thick ascending tubule, and at lower levels in the distal convoluted tubules.…”
Section: Selected Recent Regulators Of Epithelial Sodium Channel Func...mentioning
confidence: 99%
“…However, another study found that inhibition of Epac can treat hypertension caused by epithelial Na + channel over-activation. Although more careful and long-term studies are needed to confirm the efficacy and safety of Epac inhibitors ( Tomilin et al, 2022 ), the potential therapeutic effect of Epac in renal diseases has attracted increasing interest from researchers.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…The etiology is complex, making their diagnosis and treatment difficult. Despite their different expression levels, current studies show that both Epac1 and Epac2 are critical for kidney function adjustment (Cherezova et al, 2019;Tomilin et al, 2022). Chronic kidney disease (CKD), characterized by renal fibrosis, is a global health problem.…”
Section: Kidney Diseasesmentioning
confidence: 99%